2020
DOI: 10.1097/brs.0000000000003799
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Long-term Effect of Radiofrequency Denervation in Patients with Clinically Diagnosed Cervical Facet Joint Pain

Abstract: Study Design. Multicenter double-blind randomized sham-controlled trial. Objective. To assess the efficacy of radiofrequency (RF) denervation of the cervical facet joints in chronic cervical facet joint pain. Summary of Background Data. One randomized controlled trial showed efficacy of RF denervation in whiplash-associated disease. There are no randomized controlled trials on RF denervation in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…In the absence of a reference standard for degenerative CFJ pain, we defined in a study on interventions for degenerative CFJ pain that at least three of the five described degenerative features had to be present assuming an interdependent association between CFJ degeneration and other radiographic cervical degenerative abnormalities. 45 This assumption has to be substantiated with future research.…”
Section: Discussionmentioning
confidence: 97%
“…In the absence of a reference standard for degenerative CFJ pain, we defined in a study on interventions for degenerative CFJ pain that at least three of the five described degenerative features had to be present assuming an interdependent association between CFJ degeneration and other radiographic cervical degenerative abnormalities. 45 This assumption has to be substantiated with future research.…”
Section: Discussionmentioning
confidence: 97%
“…The Spine Intervention Society (SIS) and the American Society of Interventional Pain Physicians (ASIPP) have published guidelines on the performance of cervical facet blocks and RFA, 18 27 but these rigorous criteria have not been followed in recent randomized controlled and uncontrolled trials (RCTs). 19 28 Whereas stringent selection criteria have been associated with high medial branch RFA success rates, 21 the increased false-negative rate that inevitably accompanies strict diagnostic criteria and a host of other factors have resulted in an urgent need for guidelines to inform cervical joint interventions in clinical practice and trials. These factors include the absence of safer and more effective alternatives for neck pain (ie, spinal fusion and chronic opioid therapy were less scrutinized when many of the previous cervical facet studies were published), the publication of few high-quality clinical trials, rising utilization which alters the risk to benefit ratio, and questions surrounding the cost-effectiveness of diagnostic paradigms, which vary from country to country.…”
Section: Special Articlementioning
confidence: 99%
“…There have been three double-blind trials that evaluated outcomes of cervical MBB in the context of a ‘sham-controlled’ study. Van Eerd and colleagues [ 28 ] randomized 76 patients with presumptive facetogenic pain based on historical and physical examination findings to receive cervical MBB at three contiguous levels with 0.5 mL bupivacaine and sham RFA, or the same volume of bupivacaine and true RFA. In the RFA group, the mean average neck pain score decreased from 6.8 to 3.6 and 3.8 at 3- and 6-month follow-ups, respectively.…”
Section: Question 9: Do Intra-articular Facet Blocks or Medial Branch Blocks Confer Therapeutic Value?mentioning
confidence: 99%
“…In describing their results using a new posterior oblique approach for cervical facet RFA, van Eerd et al [ 298 ] reported that 51% of 65 patients were much or very much improved at 2 months. A later double-blind randomized trial performed in 76 patients with axial neck pain reported ≥50% success rates based on meaningful reduction in pain scores in both the RFA group (56%) and the LA block-sham RFA group (51%) at 6-month follow-up [ 28 ] Earlier, in a randomized trial by Stovner et al [ 103 ] that failed to enroll their intended sample size, 12 patients were allocated to true and sham denervation of the medial branches innervating the C2–6 facet joints. Although patients underwent medial branch and occipital nerve blocks before treatment, the results were not used to select participants.…”
Section: Question 14: How Many Prognostic Blocks Should One Perform Before Rfa?mentioning
confidence: 99%
See 1 more Smart Citation